2021
DOI: 10.3390/foods10051006
|View full text |Cite
|
Sign up to set email alerts
|

Combined Hot Air, Microwave, and Infrared Drying of Hawthorn Fruit: Effects of Ultrasonic Pretreatment on Drying Time, Energy, Qualitative, and Bioactive Compounds’ Properties

Abstract: The present study aimed to examine the effect of ultrasonic pretreatment and hot air, microwave–hot-air, infrared–hot air, and freeze-drying on the drying time, specific energy (SE), qualitative properties (i.e., color, shrinkage, and rehydration ratio), and bioactive compounds’ properties (i.e., antioxidant activity, phenolic, and flavonoid contents) of hawthorn fruit. Drying of hawthorn was conducted from 45 min for the ultrasonic + microwave–hot-air drying to 1280 min for the freeze-drying method. The lowes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 64 publications
1
19
0
Order By: Relevance
“…Denaturation of polyphenols was occurred during the heating process, inhibiting its activity by the increasing activity of polyphenol oxidase that was enhanced by the increasing temperature (Zhang et al, 2017). However, freeze‐dried okra exhibited the highest TFC compared to other drying method, which were similar to the study on the drying of hawthorn (Abbaspour‐Gilandeh et al, 2021), persimmon (Kayacan et al, 2020), and broccoli (Xu et al, 2020). Low temperature used during the process of freeze‐drying decreased the degradation rate of the heat‐sensitive phenolic compounds (Xu et al, 2021).…”
Section: Resultssupporting
confidence: 87%
“…Denaturation of polyphenols was occurred during the heating process, inhibiting its activity by the increasing activity of polyphenol oxidase that was enhanced by the increasing temperature (Zhang et al, 2017). However, freeze‐dried okra exhibited the highest TFC compared to other drying method, which were similar to the study on the drying of hawthorn (Abbaspour‐Gilandeh et al, 2021), persimmon (Kayacan et al, 2020), and broccoli (Xu et al, 2020). Low temperature used during the process of freeze‐drying decreased the degradation rate of the heat‐sensitive phenolic compounds (Xu et al, 2021).…”
Section: Resultssupporting
confidence: 87%
“…Based on the literature review, it can be concluded that the TPC values may range from 2.9 mg GAE/g d.w. [40] to 96.9 mg GAE/g d.w. depending on the species [41]. Abbaspour-Gilandeh et al [42] showed that the TPC value was 79.82 ± 2.42 mg GAE/g d.w. in fresh hawthorn fruits. Żurek et al [16] extracted shredded and previously freeze-dried berries from hawthorn with ethanol in two concentrations (50 and 70% v/v).…”
Section: Discussionmentioning
confidence: 98%
“…When drying foods, a very important factor is to achieve good quality indicators such as color, flavor, texture, nutrient availability, among others; all of which determine the food’s value and consumer acceptance on dehydrated food products [ 7 ]. However, in most cases, these conventional drying methods produce inferior quality products and require higher drying times [ 7 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%